1991
DOI: 10.1136/gut.32.9.1011
|View full text |Cite
|
Sign up to set email alerts
|

Deoxyribonucleic acid amplification and hybridisation in Crohn's disease using a chlamydial plasmid probe.

Abstract: The possibility that Crohn's disease is caused by infection with Chlamydia trachomatis was examined by probing for chlamydial plasmid deoxyribonucleic acid (DNA) in DNA extracts

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
1

Year Published

1994
1994
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 28 publications
1
10
1
Order By: Relevance
“…We believe that this is the first study in which the presence of C. pneumoniae in the human intestinal mucosa has been systematically examined although the possibility that Chlamydia , particularly C. trachomatis, might play an important role in human IBD has been considered from time to time in the past 12,20 . The finding of intestinal Chlamydia in pigs 32 provided the impetus to search for Chlamydia in the intestine of patients with IBD.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…We believe that this is the first study in which the presence of C. pneumoniae in the human intestinal mucosa has been systematically examined although the possibility that Chlamydia , particularly C. trachomatis, might play an important role in human IBD has been considered from time to time in the past 12,20 . The finding of intestinal Chlamydia in pigs 32 provided the impetus to search for Chlamydia in the intestine of patients with IBD.…”
Section: Discussionmentioning
confidence: 97%
“…Several groups have in the past investigated the presence of Chlamydiae organisms, mainly C. trachomatis , in patients with IBD 11,12 . Antibodies against Chlamydia of the lymphogranuloma‐venereum type were detected in 69% of 55 patients with Crohn's disease, while only two of 21 patients with other gastrointestinal (GI) disorders and one of 50 healthy blood donors had weak antibody responses 13 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…and Crohn's disease. McGarity et al, using a chlamydia plasma probe and PCR, found no evidence of C. trachomatis in 5 resection specimens and 5 biopsies from CD patients [16]. Employing a PCR-EIA method for the 16S rRNA gene of C. trachomatis on mucosal biopsies Chen et al found one positive colon in 11CD patients and one positive colon in 37 controls [17].…”
Section: Discussionmentioning
confidence: 99%